Meningkatkan Hasil Belajar Bahasa Indonesia dalam Materi Membaca Menindai dengan Menerapkan Metode STAD pada Siswa - Verry Lorensus (Publikasi Indonesia, 2022)
The problem in this study is whether using the Picture and Picture learning model can improve students' skills in simple reading in Grade XI (Even Semester) Students at Lawe Sigala-Gala Public High School in the Academic Year 2021/2022? The purpose of this study was to improve students' skills in reading simple sentences through the Picture and Picture learning model. The method used in this research is a class action research method (PTK) which is analyzed descriptively qualitatively with the aim of describing the circumstances or phenomena that occur with a focus on the problems studied which involve improving students' skills in reading simple sentences through the STAD learning model in Class XI students. (Even Semester) at Lawe Sigala-Gala Public High School for the 2021/2022 Academic Year. This research was conducted in two cycles with the material of writing simple sentences. Based on research in cycle I of 24 students who obtained the skilled category there were 12 students or 50%, so research in cycle I still needed to be continued at the next cycle stage (cycle II) because it had not yet reached the set indicators. Research in cycle II experienced an increase from 24 students who received the skilled category, there were 18 students or 75% in the Class of Class XI Students (Even Semester) at Lawe Sigala-Gala State High School in the 2021/2022 Academic Year. With these results, it means that there is no need to carry out research in the next cycle because it has reached the set indicators. The conclusion of this study is that using the Picture and Picture learning model can improve students' skills in reading simple sentences in Grade XI (Even Semester) Students at Lawe Sigala-Gala Public High School in the 2021/22 Academic Year.